A adolescente de baixa renda em situação de mãe recente: uma representação de família - Nunes, Marcos Antonio de Andrade (2007)
The family is the first social group of the individual. Group this that is of great importance, a time that all the future social relations will have it as base. The adolescent who becomes mother lives two transformations: one of the proper phase, that makes possible it new conquests and a bigger independence of its original family; another one, the condition of the maternity that points to the formation of a new familiar nucleus, causing responsibilities for which duly it is still not prepared. This study had for objective to understand how the low income adolescent in the condition of recent mother, represents the family. Our research was of qualitative nature. Twelve adolescents had participated who had given to the light its children have less of one year. We use two instruments for the material collection: the first one considered on the application of Test of the Drawing the Family with histories; and the second one, the application of an interview half-structuralized with an initial question: What family is for you? With the test application and the interview was possible to identify four thematic nucleus: family representation; family configuration; the place of the child s father in the adolescent s life and projects for the future. We evidence that these adolescents still privilege a family representation in the molds of the traditional conjugal family and that it has an association of positive feelings in relation to its. We observe that the adolescents who count on the familiar support act better as mother, even that live in a not traditional family configuration. The father s place continues conserved, ideally, even that the function presents fragile. The plans for the future are: come back to study and work to take care better of the son. From the gotten results, we detach the importance of developing programs together to the schools, health s ranks and spaces the work with adolescents, with subjects directed to the sexuality, contraception and family. As well as, a work with the grandparents who take care of its grandsons, in the direction to offer orientation and support.